Evidence for a short period of hydrologic activity in Newton crater, Mars, near the Hesperian‐Amazonian transition. Issue 5 (24th May 2013) - Parsons, R. A.; Moore, J. M.; Howard, A. D.
Abstract : [1] Hesperian/Amazonian‐aged valleys and alluvial fans distributed in regional clusters throughout the southern middle‐ to low‐latitudes were formed during a period of fluvial runoff and erosion which acted over a smaller spatial and temporal scale than the older, "classical" Martian valley networks dated to the Noachian‐Hesperian boundary. In order to explore the potential sources of water which formed these younger valleys, we calculated the expected sediment transport and water discharge rates for a valley and alluvial fan located in Newton crater (40°S, −159°E) over a wide range of water‐filled channel depths and sediment grain sizes in order to constrain the formation timescale and required water volume. Depending on the depth of the water‐filled channel within the valley, the alluvial fan was likely emplaced over ∼0.1 to ∼10 years of fluvial activity involving between 1.8 and 5.7 km 3 of water. These results imply water runoff rates of between 1 and 10 cm/d over a typical 300 km 2 drainage area. Possible processes for delivering water to these drainages include high obliquity snowpack melting via volcanism or impacts resulting in either scattered, local to regional melting events or a brief global warming event. An extended, perhaps episodic, period of fluvial activity lasting hundreds of years driven by insolation‐induced melting of high obliquity snowpacks is another possibility. Key Points: Fluvial activity lasted less than hundreds of years, likely ~10 yrs A distributed water source (e.g. snowpack) supplied ~1 to 10 cm/day of runoff Either scattered local melting or global warming/melting via volcanic or impacts